Classification and study of the clinico-hematological profile of patients with dengue fever in the pediatric age group - Mogra, Gaurav; Ghildiyal, Radha Gulati; Mohanlal, Smilu (International Journal of Contemporary Pediatrics, 2016)
Background:Dengue fever has become a major public health issue constituting a major burden of monsoon related illnesses. New WHO classification of dengue fever was introduced in 2009. There is a need to study the factors which can predict the severity of dengue fever for timely interventions and management to decrease the mortality and morbidity. Methods: An observational prospective study was conducted in the pediatric ward and intensive care unit at a tertiary care center in Mumbai to study the correlation between severity and clinical and laboratory parameters, morbidity and mortality in patients with dengue fever. The qualitative data was represented in the form of frequency and percentage tables with the help of SPSS 17. Results:This study spanning an 18 month period enrolled 100 hospitalized patients.45% of them were classified as probable dengue, 44% as dengue with warning signs and 11% were severe dengue. 64% had a normal nutritional status, 28% moderate malnutrition and 8% severe malnutrition. Most common symptom was fever in 100% children, 57% vomiting, 50% rash, 49% malaise, 44% abdominal pain, 45% headache, 37% petechiae, 26% bleeding manifestation, 3% altered sensorium and 2% convulsion.46% of them had hepatomegaly ,45% with positive tourniquet test, 17 % tachycardia, 10% splenomegaly, 8% signs of circulatory failure and 7% had hypotension. Of the laboratory parameters 72% had abnormal total counts, 58% with thrombocytopenia, 45% deranged liver function tests, 41% had hemoconcentration, 22% deranged renal function test, 13% electrolyte disturbances and 6% metabolic acidosis.48% had pleural effusion and 33% had ascitis. The mortality rate was 2%. Conclusions:A significant association (p<0.05) was found between abdominal pain, petechiae, bleeding manifestation, altered sensorium, convulsion, tachycardia, hypotension, hepatomegaly, splenomegaly, signs of circulatory failure, positive tourniquet test, hemoconcentration, platelet count, electrolyte disturbances, deranged liver and renal function tests, pleural effusion, ascitis and duration of stay with severity of dengue fever.